2016
DOI: 10.1111/ejn.13242
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural evidence for separate mechanisms of audiovisual temporal binding as a function of leading sensory modality

Abstract: The ability to integrate auditory and visual information is critical for effective perception and interaction with the environment, and is thought to be abnormal in some clinical populations. Several studies have investigated the time window over which audiovisual events are integrated, also called the temporal binding window, and revealed asymmetries depending on the order of audiovisual input (i.e. the leading sense). When judging audiovisual simultaneity, the binding window appears narrower and non-malleabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 48 publications
4
27
0
Order By: Relevance
“…The CIs revealed that the A50V point (73 ± 16 ms) was estimated with higher precision than the V50A point (82 ± 27 ms; t (26) = 2.14, P = 0.04), suggesting less reliability for time estimation of vision leading trials compared to audition leading trials (individual data are reported in Supplementary Table S1). This results are well in line with previous results showing that synchrony perception has greater tolerance and flexibility for vision leading than audition leading asynchronies (Cecere et al., ; Stevenson & Wallace, ; Van Eijk et al., ; Yarrow et al., ). This result can be considered as evidence for the reliability of each sensory modality on our simultaneity judgement task.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The CIs revealed that the A50V point (73 ± 16 ms) was estimated with higher precision than the V50A point (82 ± 27 ms; t (26) = 2.14, P = 0.04), suggesting less reliability for time estimation of vision leading trials compared to audition leading trials (individual data are reported in Supplementary Table S1). This results are well in line with previous results showing that synchrony perception has greater tolerance and flexibility for vision leading than audition leading asynchronies (Cecere et al., ; Stevenson & Wallace, ; Van Eijk et al., ; Yarrow et al., ). This result can be considered as evidence for the reliability of each sensory modality on our simultaneity judgement task.…”
Section: Resultssupporting
confidence: 93%
“…This larger perceptual variability for vision‐first events has been noted in many previous psychophysical studies, when asymmetries have been sought for (Yarrow et al., ), and is probably related to the well known lower sensitivity in asynchrony detection when vision leads audition (Cecere, Gross, Willis, & Thut, ; Conrey & Pisoni, ; Stevenson & Wallace, ; Van Wassenhove et al., ). A second, perhaps complementary, explanation for the asymmetry in our results, is that synchrony perception of different modality orders might rely on distinct, partially non‐overlapping (modality specific) neural processes (Cecere et al., , ; Thorne & Debener, ). This explanation might not seem parsimonious at first, but its plausibility is supported after recent findings of analogous asymmetries in synchrony processing across different modality orders in other electrophysiological studies (Kaganovich & Schumaker, ; Kösem et al., ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…As the speed of speech increases, the importance of visual precedence for intelligibility becomes even more pronounced (Brungart, Iyer, Simpson, & Wassenhove, 2008), suggesting that this asymmetry is tuned to allow maximal comprehension of rapid conversational speech. This asymmetrical resizing of AV integration window may proximally result from separate auditory and visual initiated processes (Munhall & Tohkura, 1998; Cecere, Gross, & Thut, 2016; van Wassenhove, 2013) – a view consistent with the Dynamic Reweighting Model.…”
Section: Discussionmentioning
confidence: 56%